GE_GERICHTE P/6453/2016 vom 9. November 2016 - GE Cour de justice (2016)
DÉTENTION DE STUPÉFIANTS ; TRANSPORT DE STUPÉFIANTS ; ENTRÉE DANS UN PAYS ; PASSEUR ; DÉTRESSE | LStup.19.1.2 LEtr.115.1 A CP.47 CP.49